Is it possible to construct Pancasila within a hierarchy of legal regulations? - Edi Haskar; Raju Moh Hazmi (Civiliza Publishing, 2026)
This study aims to provide an explanation regarding the existential issue of Pancasila. This issue focuses on whether Pancasila can be explicitly included in the hierarchy of legislation, so that the first level of legislation in Article 7 paragraph (1) of Law 12/2011 is Pancasila. Is it ontologically possible for Pancasila to be present in the hierarchy as part of legal norms (axioms/postulates that have undergone positivization)? To uncover this legal issue, normative research was conducted using philosophical, conceptual, and legislative approaches. The data used are secondary data, including primary, secondary, and tertiary legal materials. Data analysis will be presented descriptively and qualitatively through content analysis. The results of this study found that Pancasila exists as the basis of the state; it is a fundamental reality of values, grundvalues, and rechtsidee/staatfunamentalnorm, which inspires, provides purpose, and serves as a measure for the creation and validity of positive norms. Thus, Pancasila is not at the level of legal products, but at the level of the foundation of legal meaning; It is a foundation (foundation) and not the basis itself. Pancasila is not suitable to be positioned as a 'norm level' in the hierarchy because it is not part of a series of positive norms. The implications of including Pancasila in the legal hierarchy are (1) a change in the category of Pancasila from grundnorm/source to object of the hierarchy, (2) the potential for Pancasila to be changed, and (3) the need for an overhaul of the norm testing architecture.